The myth of morality - Joyce, Richard (Cambridge University, 2013)
In The Myth of Morality, Richard Joyce argues that moral discourse is hopelessly flawed. At the heart of ordinary moral judgments is a notion of moral inescapability, or practical authority, which, upon investigation, cannot be reasonably defended. Joyce argues that natural selection is to blame, in that it has provided us with a tendency to invest the world with values that it does not contain, and demands that it does not make. Should we therefore do away with morality, as we did away with other faulty notions such as witches? Possibly not. We may be able to carry on with morality as a useful fiction - allowing it to have a regulative influence on our lives and decisions, perhaps even playing a central role - while not committing ourselves to believing or asserting falsehoods, and thus not being subject to accusations of error.